Analisis Faktor-Faktor yang Memengaruhi Penanganan Pada Anak Autis di SLB Aneuk Nanggroe dan Cinta Mandiri kota Lhoksemawe Provinsi Aceh - Mailinda wati; Khairul Azwar; Eka Sutrisna (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Autism is a collection of developmental disorders characterized by difficulty interacting socially, verbal and nonverbal communication problems, accompanied by repetitive behaviors and shallow and obsessive interests. Autism has an impact on children as well as on families. The impact on children is poor school achievement, low work status, health problems suffered, psychosocial impacts (needs for comfort, needs to be loved and loved, needs for self-esteem, self-actualization and impaired social interaction) and increased risk of accidents. The impact on the family is the emergence of severe stress and depression on parents and caregivers so that it affects harmony in the household. Handling autistic children must be holistic, such as diet therapy, occupational therapy, speech therapy and biomedicine, if done incompletely and separately the results are not optimal. The purpose of the study was to analyze the factors that influence the treatment of autistic children.Type of observational analytic research with cross-sectional study design. The subject of the research trial with a population of 31 people in SLB Aneuk Nanggroe and Cinta Mandiri, Lhoksemawe City, Aceh Province. The instrument in this study was made in the form of a questionnaire. Data were analyzed using linear regression and chi square for bivariate and multivariate analysis using multiple logistic regression (logistic binary regression).Results of research conducted from April to August 2021. The results of the chi-square test at the level of significant = 0.05 indicate that there is a relationship between parenting style and handling of autistic children (p value 0.04) or pË‚0.05, there is no relationship between diet and treatment of autistic children (p value 0.06) or pËƒ 0.05 and there is a relationship between social stories therapy and the treatment of autistic children (p value 0.04) or pËƒ0.05. Mandatory output in the form of an accredited national journal. The Technology Readiness Level of this research is 2.